Pengaruh tingkat literasi media terhadap tingkat self-esteem pada peserta didik di SMP Negeri 214 Jakarta - Dwi Fitriyani (Pusat Kajian Bimbingan dan Konseling FIPPS Unindra, 2019)
The media has a very important function in providing information needs for each individual. Media that contains content that is negative to the community can have an adverse effect on the formation of people's perceptions in decision making. Regarding this, mass media users need other options in order to be protected from the various influences of mass media and require individuals to be smarter using media. This study aims to determine the level of media literacy on the self-esteem of students at 214 Public Middle Schools Jakarta. The method used in this study is a quantitative method with a clause associative approach. Data analysis technique is done by tabulating data according to students' answers to the questionnaire, then calculated using the Simple Linear Regression formula. The results of the study concluded that Media Literacy influences students' self-esteem, this is evidenced through hypothesis testing which is known to have a significance value of less than <0.05 with a value of 0.009, in addition it is known that the R Square value of 0.091. This value means that the influence of Media Literacy (X) on Self-Esteem (Y) is 9.1%. From the results of the hypothesis test, it can be concluded that media literacy has a positive effect of 9.1%, which means increasing student media literacy will affect the increase in self-esteem